2021
DOI: 10.3389/fnut.2021.746880
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Fish Consumption and Muscle Mass and Function in Middle-Age and Older Adults

Abstract: Background: Sarcopenia, the age-related loss of skeletal muscle mass and function, represents a crucial risk factor for disability and mortality. Increasing intake of some nutrients, particularly protein and omega-3 fatty acids seems to be a promising strategy to augment muscle mass and function.Objective: The purpose of this study was to assess the beneficial effects of fish consumption on muscle mass and function among middle-age and older adults.Methods: Twenty-two adults aged 50–85 years participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Considering that PhA reflects muscle quality [ 28 ], a recent study examining the actual benefits of fish consumption in terms of the beneficial effects of the biological compounds contained in fish on muscle mass found that fish consumption has a protective and anti-inflammatory effect on skeletal muscle mass [ 49 ]. A previous study also demonstrated that the consumption of fish twice weekly over a 10-week period resulted in a significant increase in skeletal muscle mass and appendicular lean mass [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that PhA reflects muscle quality [ 28 ], a recent study examining the actual benefits of fish consumption in terms of the beneficial effects of the biological compounds contained in fish on muscle mass found that fish consumption has a protective and anti-inflammatory effect on skeletal muscle mass [ 49 ]. A previous study also demonstrated that the consumption of fish twice weekly over a 10-week period resulted in a significant increase in skeletal muscle mass and appendicular lean mass [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fish are an important component of diet worldwide because they greatly improve overall health with their rich nutritional profiles. With widespread recognition of the preventive effects of fish consumption on diseases such as muscle wasting-induced sarcopenia through large-scale cohort studies, fish-based diets are gradually gaining popularity [ 19 , 20 , 21 ]. However, as fish consumption increases, appropriate utilization of fish processing by-products remains limited [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plasma levels of n-3 PUFA were associated with faster gait speed in Italian women at a 3-year follow-up ( 48 ), and with lower risk of mobility disability, defined as having difficulty in walking or climbing steps, in older Icelandic women ( 49 ). Alhussain et al ( 50 ) reported that gait speed increased significantly after consumption of fish during 10 weeks in older Saudi Arabian adults. A meta-analysis of clinical studies revealed that n-3 PUFA supplementation improved gait speed in older Americans and Europeans ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the intake of total seafood and fish was associated with handgrip strength at baseline and at the 4-year follow-up. Consumption of fish significantly increased handgrip strength in older Saudi Arabian adults ( 50 ). A meta-analysis of the clinical studies also showed that n-3 PUFA supplementation improved handgrip strength in older Americans and Europeans ( 14 ).…”
Section: Discussionmentioning
confidence: 99%